2004
DOI: 10.1016/j.physa.2004.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The durations of recession and prosperity: does their distribution follow a power or an exponential law?

Abstract: Following findings by Ormerod and Mounfield [1] Wright [2] rises the problem whether a power [1] or an exponential law [2] describes the distribution of occurrences of economic recession periods. In order to clarify the controversy a different set of GDP data is hereby examined. The conclusion about a power law distribution of recession periods seems better though the matter is not entirely settled. The case of prosperity duration is also studied and is found to follow a power law. Universal but also non unive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 15 publications
(45 reference statements)
3
21
0
1
Order By: Relevance
“…the second column of Table 1). Moreover, in line with Ausloos et al (2004), the large majority of economic crises are short-lived, lasting only one period, but few downturns have a long duration. As a consequence, the model-generated distribution of recession durations is exponential well in line with the empirical evidence (cf.…”
Section: Accounting For Mild and Deep Recessionsmentioning
confidence: 85%
“…the second column of Table 1). Moreover, in line with Ausloos et al (2004), the large majority of economic crises are short-lived, lasting only one period, but few downturns have a long duration. As a consequence, the model-generated distribution of recession durations is exponential well in line with the empirical evidence (cf.…”
Section: Accounting For Mild and Deep Recessionsmentioning
confidence: 85%
“…In line with Ausloos et al (2004), the large majority of economic crises are short-lived, lasting only one period. Moreover, the distribution of recession durations is exponential (Wright, 2005) Finally, the model is also able to replicate a large array of microeconomic empirical regularities (see e.g.…”
Section: Empirical Validationmentioning
confidence: 87%
“…Recessions tend not to last longer than 6 years, the majority of recessions last 1 year, and for the US the longest recession has been only 4 years (Ormerod, 2002). Ausloos et al (2004) subsequently analyzed a more comprehensive set of GDP data and concluded that overall the durations more closely follow a power-law, not an exponential law. In the light of this more extensive data set we must conclude that the CSA model only approximately replicates the empirical distribution.…”
Section: Duration Of Recessionsmentioning
confidence: 99%